Perspectives upon Integrating Music into Freshman English Pronunciation Training Classroom - Chen, Ai-Hwa (Asian Journal of Education and Training, 2016)
This study explores the effects of integrating music into English pronunciation practice. Ninety-five English major students from a technological university located in central Taiwan participated in this project. Six songs were selected and played by means of using YouTube. Students were given a list of vocabulary words selected from the lyrics and learned pertinent pronunciation rules that were augmented with phonetic symbols. They were asked to take quizzes that required memorizing the song’s lyrics. The findings point out that almost all students enjoyed listening to songs and indicated that they had become more familiar with many English songs and the rules of pronunciation by practicing singing and memorizing the lyrics.